Tuberculosis Prevention Measure from an Environmental Factors Perspective and the Role of Health Workers: - - Kurniawati, Ratna Dian; Setiawati, Rita; Setiani, Onny; Martini (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Tuberculosis (TB) is an environmentally transmitted disease caused by Mycobacterium tuberculosis. The second Tuberculosis position in the world is occupied by Indonesia after India. In 2024, the incidence of TB in men was recorded at 496 thousand cases, women with TB at 359 thousand, and children aged 0-14 years as many as 135 thousand cases. This condition requires attention in prevention efforts throughout Indonesia. The study aimed to analyze environmental factors and the role of health workers associated with TB prevention measures. Analytical observational research with a cross-sectional approach was conducted among 1,947 people, and a proportional random sample of 92 residents was drawn. Data analysis using the Chi-Square test obtained lighting (P-value=0.021), humidity (P-value=1.000), temperature (P-value=0.939), occupancy density (P-value=0.040), and the role of health workers (P-value=0.002). The study concludes that there is an association between lighting, occupancy density, and the role of health workers in TB prevention efforts. The variables that did not have an association with TB prevention measures were humidity and temperature. The results of this study can provide input for improving TB prevention and control programs that collaborate across programs and sectors. This includes enhancing outreach and strengthening the role of health cadres and community organizations to encourage communities to improve their physical home environments to create healthy, TB-free homes